TERRITORIAL AND TEMPORAL DYNAMICS OF TANGERINE (CITRUS RETICULATA) PRODUCTION IN BRAZIL BETWEEN 1970 AND 2020 - Alves Dias, Deilson; Dutra Alves, Flamarion (Ra'e Ga: o Espaço Geográfico em Análise, 2025)
The geographical distribution of tangerine (Citrus reticulata) plantations in Brazil underwent significant changes between 1970 and 2020, reflecting territorialization, deterritorialization, and reterritorialization. This study analyzes the spatial dynamics of tangerine cultivation in Brazil based on data from the Municipal Agricultural Production survey (PAM/IBGE), using a quali-quantitative approach that focuses on planted area and production volume, and applies decadal averages for each municipality, associated with the construction of thematic maps and the comparison of historical series, which made it possible to identify patterns of continuity and disruption in production and to map the shifts of the main production areas over the decades. The research identified the initial consolidation of citriculture in the state of São Paulo, followed by a decline due to diseases such as greening, and the emergence of new production centers in Minas Gerais, Paraná, and Rio Grande do Sul. The spatial analysis revealed that tangerine production shifts according to environmental, phytosanitary, and economic factors, affecting the permanence of orchards in certain territories. It is observed that production concentration in some regions fosters agricultural specialization but also amplifies sanitary vulnerabilities inherent to the activity. The study concludes that tangerine citriculture in Brazil is marked by a constant cycle of territorial reorganizations, driven both by phytosanitary challenges and by productive strategies aimed at competitiveness and adaptation to new sectoral conditions.